2013
DOI: 10.7224/1537-2073.2012-035
|View full text |Cite
|
Sign up to set email alerts
|

Headache in Multiple Sclerosis

Abstract: The aim of this study was to investigate the variables affecting headache occurrence in patients with multiple sclerosis (MS). Seventy-two MS patients with comorbid headaches completed a 28-item questionnaire. This evaluation assessed each patient's demographics, headache description and modifying factors, social history, and impact on quality of life. Our patients reported a wide spectrum of headache presentations, characteristics, and resulting disability. We discuss the patterns in our data in the context o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 21 publications
(10 citation statements)
references
References 20 publications
0
10
0
Order By: Relevance
“…The relationship between migraine and the disease activity was investigated by a study of Tabby et al ( 2013 ), who showed that MS patients with migraine presented more relapses than patients without migraine and that 85% of patients whose attacks were often or always of severe intensity reported a headache worsening during MS exacerbations. Furthermore, Kister et al ( 2010 ) observed that migraine in MS patients was significantly associated with a more symptomatic course of the disease, but not with disability or T2 lesion burden on brain magnetic resonance imaging (MRI).…”
Section: Immunological Disorders and Migrainementioning
confidence: 99%
“…The relationship between migraine and the disease activity was investigated by a study of Tabby et al ( 2013 ), who showed that MS patients with migraine presented more relapses than patients without migraine and that 85% of patients whose attacks were often or always of severe intensity reported a headache worsening during MS exacerbations. Furthermore, Kister et al ( 2010 ) observed that migraine in MS patients was significantly associated with a more symptomatic course of the disease, but not with disability or T2 lesion burden on brain magnetic resonance imaging (MRI).…”
Section: Immunological Disorders and Migrainementioning
confidence: 99%
“…These results are comparable with other studies. In a work of Tabby, Majeed, Youngman, & Wilcox (), throbbing headaches were found in 52.9% patients as the most frequent form in 72 MS patients with headaches. D'Amico et al.…”
Section: Discussionmentioning
confidence: 95%
“…MS patients who associate migraine headaches seem to have typical migraine characteristics but with a more important severity regarding the intensity of pain and a high frequency of headache attacks [13]. The most frequent headache triggers described in the studies were fatigue and stress [8]. It has also been shown that stress precipitates MS exacerbations.…”
Section: Types Of Headaches In Multiple Sclerosis Patientsmentioning
confidence: 89%
“…There have been rare instances of cluster-type headaches reported among these patients. The infrequency of cluster-type headaches in this context could be attributed to their low prevalence in the general population [8,9]. Migraines associated with multiple sclerosis represent the subject of many studies.…”
Section: Types Of Headaches In Multiple Sclerosis Patientsmentioning
confidence: 99%